2006
DOI: 10.1177/1066480706287809
|View full text |Cite
|
Sign up to set email alerts
|

Feeling the Tug: Creative Use of Ropes and Felt Board to Promote Family Change

Abstract: Experiential metaphor has been used in marriage and family therapy for many years. One example of metaphor application involves the use of ropes and felt board to identify and explore relationships in families. In this case, the mother of a son who was socially isolated is treated by a marriage and family therapy intern, using ropes and felt board as media to exemplify the tugs of relationships, demands, and expectations. Responding to the metaphors, the mother changed relationships with her son, other childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Additionally, just as Bruhn et al . () prescribed family sculpture to reframe the families' interpersonal structures, therapists in our study also adopted spatialization and gesture similar to family sculpture to achieve reframing (see examples from F1 and F7). All the above findings reflect the integration of Chinese culture with western‐imported family therapy methods and the important role that metaphor plays in Chinese family therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, just as Bruhn et al . () prescribed family sculpture to reframe the families' interpersonal structures, therapists in our study also adopted spatialization and gesture similar to family sculpture to achieve reframing (see examples from F1 and F7). All the above findings reflect the integration of Chinese culture with western‐imported family therapy methods and the important role that metaphor plays in Chinese family therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, results showed that Chinese therapists would adopt stories from both Chinese history (such as the story of Xu Shu jin Cao ying in F15) and biographies of Chinese famous figures (such as the story of Mao Zedong in F2), and foreign novels (for example, 'The Adventure of Tom Sawyer' in F16) to facilitate the families' awareness and change in beliefs. Additionally, just as Bruhn et al (2006) prescribed family sculpture to reframe the families' interpersonal structures, therapists in our study also adopted spatialization and gesture similar to family sculpture to achieve reframing (see examples from F1 and F7). All the above findings reflect the integration of Chinese culture with westernimported family therapy methods and the important role that metaphor plays in Chinese family therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining traditional talk counseling with creative interventions offers clients new and creative perspectives to explore their concerns (Metzl, 2020) and access information which they may have trouble verbalizing (Bruhn et al, 2006). Gottman and Silver (2015) note that playful activities can be used as a mechanism to build and cultivate friendship in couple relationships when little foundation seems existent.…”
Section: Creativity and Rct Couples Counselingmentioning
confidence: 99%